A Study of Gestures in a Video-Mediated Collaborative Assembly Task. (16th January 2011) - Alem, Leila; Li, Jane
Abstract : This paper presents the results of an experimental investigation of two gesture representations (overlaying hands and cursor pointer) in a video-mediated scenario—remote collaboration on physical task. Our study assessed the relative value of the two gesture representations with respect to their effectiveness in task performance, user's satisfaction, and user's perceived quality of collaboration in terms of the coordination and interaction with the remote partner. Our results show no clear difference between these two gesture representations in the effectiveness and user satisfaction. However, when considering the perceived quality of collaboration, the overlaying hands condition was statistically significantly higher than the pointer cursor condition. Our results seem to suggest that the value of a more expressive gesture representation is not so much a gain in performance but rather a gain in user's experience, more specifically in user's perceived quality of collaborative effort.